Az eva tapasztalatai vállalkozói interjúk alapján - András Semjén; István János Tóth; Mihály Fazekas (Hungarian Academy of Sciences, Institute of Economics, 2008)
– By introducing simplified enterprise tax or eva in 2003, the government had a double aim: it wanted to relieve administrative and tax burdens on micro and small enterprises, while at the same time it wanted to improve their tax compliance, thus increasing tax revenues received from such enterprises. Mainly enterprises with a rather low (typically below 60 per cent) cost ratio opted for eva. Our research is based on 33 structured interviews with enterprises paying their taxes under the eva rules, and it focuses on changes in their tax behavior due to switching over to eva. Our results suggest that tax evasion and avoidance has diminished in this segment of the enterprise sector. 65 % of the interviewed enterprises reported complete tax compliance and legitimate operations, which can be considered a rather high rate given the high involvement of smaller enterprises in the hidden economy. Tax evasion has decreased even among the remaining part of the interviewed enterprises under the eva: although enterprises in this group reported some minor violations of the tax laws, nevertheless even these were mainly prompted by their buyers' demand for purchasing tax free and with no invoice. The share of unreported sales remained below 1/4 of sales revenues even within this group. The empirical evidence gathered from our interviews does not support the frequently hold belief that eva after all has increased the scope of the underground economy by the emission of fictive invoices or by converting lawful employment into (pretended) subcontracting to former employees. The positive overall effect of eva on tax compliance is due to two main reasons according to our findings: most taxpayers under the eva find their tax burden fair and acceptable, while at the same time the simplicity and transparency of record-keeping and tax rules for enterprises under the eva increases the expected costs of tax evasion within this group of enterprises.
Keywords: 330; underground economy; business tax; presumptive taxation; tax compliance; tax evasion; firm behavior; economic sociology; social norms; KMU; Unternehmensbesteuerung; Steuermoral; Steuervermeidung; Schattenwirtschaft; Ungarn